2011
DOI: 10.1007/s00259-011-1888-8
|View full text |Cite
|
Sign up to set email alerts
|

Exhalation of 131I after radioiodine therapy: measurements in exhaled air

Abstract: The amount of exhaled radioiodine is small but by no means negligible on the first day after administration. This is the first study to provide experimental evidence on a systematic basis that radioiodine becomes exhalable in vivo, i.e. in the patient. The mechanism of organification of orally administered radioiodine remains to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Furthermore, a possible dose contribution by inhalation of 131 I has to be considered. Schomäcker et al demonstrated that the amount of radioiodine in the patient's exhaled air might also be a significant factor [15], not to mention the risk of extensive cutaneous contaminations. After an inpatient stay of three days which is comparable to the typical duration of 4 days in this study (Table 1), the dose attributable to inhalation reaches a maximum of about 10 µSv.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a possible dose contribution by inhalation of 131 I has to be considered. Schomäcker et al demonstrated that the amount of radioiodine in the patient's exhaled air might also be a significant factor [15], not to mention the risk of extensive cutaneous contaminations. After an inpatient stay of three days which is comparable to the typical duration of 4 days in this study (Table 1), the dose attributable to inhalation reaches a maximum of about 10 µSv.…”
Section: Discussionmentioning
confidence: 99%
“…Die Halbwertszeit liegt meist zwischen 12-24 h. Selbst bei einer Gabe von lediglich 1 GBq können bei einer Entlassung nach 48 h noch zwischen 60 und 250 MBq in die Umwelt freigesetzt werden. Mindestens genauso schwerwiegend ist jedoch die Abatmung des Radioiods [ 50 ] . Anders als bei der direkten Bestrahlung eines Mitmenschen durch den entlassenen Patienten spielt für die Inkorporation von kontaminierter Raumluft der Abstand keine Rolle [ 9 ] .…”
Section: Durchführung Der Radioiodtherapie ▼unclassified